1990
DOI: 10.1530/jrf.0.0890605
|View full text |Cite
|
Sign up to set email alerts
|

 -Endorphin and met-enkephalin in plasma of cattle during pregnancy, parturition and the neonatal period

Abstract: Plasma concentrations of beta-endorphin and met-enkephalin were measured, with appropriate radioimmunoassays, in cows during gestation and at parturition and in newborn calves. During pregnancy beta-endorphin immunoreactivity (IR) concentration increased, but values during the last month of gestation were not different from those at parturition. Highest met-enkephalin IR levels were obtained in cows during calving. A term Caesarean section caused an increase in plasma beta-endorphin and met-enkephalin IR conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 22 publications
3
16
0
1
Order By: Relevance
“…In this study, we found an increased release of ß-endorphin in parturient cows which is in agreement with previous results from different species (Csontos et al, 1979;Goland et al, 1981;Petraglia et al, 1985;Aurich et al, 1990 (Guillemin et al, 1977), in pregnant sheep submitted to hypoglycaemia, the placenta has been identified as an additional source of ß-endorphin (Falconer et al, 1988). ß-Endorphin can also be synthesized by human placental tissue (Liotta et al, 1982).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, we found an increased release of ß-endorphin in parturient cows which is in agreement with previous results from different species (Csontos et al, 1979;Goland et al, 1981;Petraglia et al, 1985;Aurich et al, 1990 (Guillemin et al, 1977), in pregnant sheep submitted to hypoglycaemia, the placenta has been identified as an additional source of ß-endorphin (Falconer et al, 1988). ß-Endorphin can also be synthesized by human placental tissue (Liotta et al, 1982).…”
Section: Discussionsupporting
confidence: 92%
“…Exogenous prostaglandin F2(J (PGF2a) has been shown to stimulate oxytocin release in postpartum sows (Ellendorff et al, 1979) and prostaglandins are involved in luteolysis and regulation of labour (Challis and Lye, 1986). We (Aurich et al, 1990). The extraction recovery for ß-endorphin was 86%.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Its rapid degradation may explain some of the variation between samples and animals. However, our results confirmed earlier findings in cows, sampled on a single occasion during parturition, in which plasma metenkephalin levels increased during labour (Aurich et al 1990, Dobrinski et al 1991. In the goats and assisted heifers, the met-enkephalin concentration correlated with that of noradrenaline and adrenaline.…”
Section: Figuresupporting
confidence: 93%